1996
DOI: 10.1007/bf01544952
|View full text |Cite
|
Sign up to set email alerts
|

Mapping protein-protein contact sites using cellulose-bound peptide scans

Abstract: We have characterized the interaction of two monoclonal antibodies with their respective antigens using cellulose-bound sets of overlapping peptides (peptide scans). Both antibodies CB/RS/5 and CB/MT/1 recognize discontinuous epitopes present in human interleukin-10 (IL-10) and tumor necrosis factor alpha (TNF-alpha). In addition, the interaction between TNF-alpha and its 55-kDa receptor (TNF-R) was investigated by the same approach. Both antibodies, as well as TNF-alpha, interacted with two or more regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 28 publications
1
31
1
1
Order By: Relevance
“…Usually the affinities of peptides spanning single ligate binding regions to the ligand are too low for competition studies. One exception is the interaction of IgM antibodies with single binding regions of nonlinear epitopes due to avidity effects ("functional affinity"), caused by multiple binding sites (Reineke et al, 1995). In our case, peptides derived from L l O as well as IL-10R were neither able to compete with this interaction nor the interaction of these two proteins with neutralizing antibodies recognizing discontinuous epitopes.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Usually the affinities of peptides spanning single ligate binding regions to the ligand are too low for competition studies. One exception is the interaction of IgM antibodies with single binding regions of nonlinear epitopes due to avidity effects ("functional affinity"), caused by multiple binding sites (Reineke et al, 1995). In our case, peptides derived from L l O as well as IL-10R were neither able to compete with this interaction nor the interaction of these two proteins with neutralizing antibodies recognizing discontinuous epitopes.…”
Section: Discussioncontrasting
confidence: 61%
“…In addition, a fourth binding region was found in both peptide scans. However, since it has been shown that peptides of this region interact with constant regions of IgM monoclonal antibodies, such as CB/RS/S (Reineke et al, 1995) this region was considered to represent unspecific binding. The fact that binding regions A, B, and C are in close vicinity on the IL-10 surface (Fig.…”
Section: Mapping Of the Il-io/il-lor Combining Sitementioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the epitope sequences are separated by more than 100 aa, as only sequences of up to 100 aa can be presented on the phage surface in this system. Since conformational epitopes can also be identified by peptide scanning (31,32,35,39), this method was employed for mapping of the A20, C24-B, C37-B, and D3 epitopes. For each antibody, specific regions of the VP3 protein sequence based on their reactivity with specific serotypes were synthesized as overlapping 10-mer peptides and probed with A20, C24-B, C37-B, or D3.…”
Section: Fig 4 Epitope Mapping Of Mabs C37-b A20mentioning
confidence: 99%
“…Liljeqvist and others J.-A H . Liljeqvist and others (Kramer et al, 1993(Kramer et al, , 1994 as well as discontinuous epitopes (Gao & Esnouf, 1996 ;Korth et al, 1997 ;Reineke et al, 1995).…”
Section: Introductionmentioning
confidence: 97%